Ram pressure candidates in UNIONS. Issue 1 (28th October 2021) - Roberts, Ian D; Parker, Laura C; Gwyn, Stephen; Hudson, Michael J; Carlberg, Raymond; McConnachie, Alan; Cuillandre, Jean-Charles; Chambers, Kenneth C; Duc, Pierre-Alain; Furusawa, Hisanori; Gavazzi, Raphael; Hill, Vanessa; et al.
ABSTRACT: We present a search for disturbed, candidate ram pressure stripping galaxies across more than 50 spectroscopically selected SDSS groups and clusters. 48 ram pressure candidates are visually identified in these systems using high-quality UNIONS imaging from the Canada-France-Hawaii Telescope, covering ${\sim }6200\, deg^2$ and ${\sim }2800\, deg^2$ in the u - and r -bands, respectively. Ram pressure candidates are found in groups and clusters spanning a wide range in halo mass and include ∼30 ram pressure candidates in the group regime ( Mh < 10 14 ). The observed frequency of ram pressure candidates shows substantial scatter with group/cluster mass, but on average is larger in clusters ($M_h \ge 10^{14}\, \mathrm{M_\odot }$ ) than groups ($M_h \lt 10^{14}\, \mathrm{M_\odot }$ ) by a factor of ∼2. We find that ram pressure candidates are most commonly low-mass galaxies and have enhanced star formation rates relative to star-forming field galaxies. The enhancement in star formation is largely independent of galaxy mass and strongest for galaxies in clusters. As a result of the large survey footprint and excellent image quality from UNIONS, we are able to identify disturbed galaxies, potentially affected by ram pressure stripping, across a wide range of host environment.